Economic and legal regulation of the use and development of renewable energy sources - Sabyrzhan, A.; Balgimbekova, G.; Shestak, V. (International Environmental Agreements-Politics Law and Economics, 2021)
The study, through the prism of comparing various government practices, critically examines the problems of Russian legislation and policies in the field of renewable energy sources, such as problems of fragmentation, obsolescence and lack of legislation. The article examines the current legislation, which establishes incentives for the development of renewable energy. The research question consists in assessing the applicability of current international practices in the field of regulation of the use of renewable energy sources in the context of the modern Russian legal system. Through the use of comparative legal method, the study analyzes foreign experience and considers the possibility of its implementation in the national legal system. The conclusion is drawn on the main directions of improving the economic and legal regulation of incentives for the development of renewable energy in Russia. In addition, the international cooperation of countries in the field of renewable energy was carefully studied, and a conclusion was drawn on the insufficient regulation of the industry by international law. Conceptually, the law on renewable energy should be based on comprehensive international energy law. From a practical point of view, different paths can create individual rules or principles for renewable energy. It is legal norms that have become the object of research. The analytical framework used in this article is based on both qualitative and quantitative methodologies. The purpose of the article is twofold: to analyze the main legal aspects of the use of renewable energy sources in Russia and to evaluate the existing political context that affects their development and settlement. The practical significance of the work done is that the results obtained can be applied in the process of making legislative acts in the field of the use and development of renewable energy sources.
Keywords: Alternative energy sources; Development of renewable energy sources; Environmental protection; Economic and legal regulation; Renewable energy; The law on renewable energy